2020
DOI: 10.1007/s00484-020-01878-0
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography for evaluation of the environmental thermal comfort for livestock

Abstract: The objective of this study was to assess the use of infrared thermography as a microclimate-evaluating tool and an estimate of the thermal comfort provided by four types of tree to cattle under grazing conditions in the central region of Brazil. The experiment was conducted at the Embrapa Beef Cattle Company, in Campo Grande, MS, Brazil, from June to August 2015. Evaluations were carried out over four consecutive days, at 1-hour intervals, from 8:00 a.m. to 4:00 p.m. (local time; GMT − 4:00). Infrared thermog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
1
8
2
Order By: Relevance
“…In addition to these two variables, they concluded that other elements –wind speed, air pressure, body weight, and food consumption– require models to determine their influence on IRT. Those findings are similar to the observations by Barreto et al ( 156 ), who found a positive correlation between solar radiation, environmental humidity, and wind with body surface temperatures.…”
Section: Infrared Thermography (Irt) As a Tool To Evaluate The Therma...supporting
confidence: 92%
“…In addition to these two variables, they concluded that other elements –wind speed, air pressure, body weight, and food consumption– require models to determine their influence on IRT. Those findings are similar to the observations by Barreto et al ( 156 ), who found a positive correlation between solar radiation, environmental humidity, and wind with body surface temperatures.…”
Section: Infrared Thermography (Irt) As a Tool To Evaluate The Therma...supporting
confidence: 92%
“…However, when this mechanism is insufficient, the rectal temperature of animals may increase (Rossarolla, 2007). Thermal imaging is also used to diagnose heat stress in animals (Barreto et al, 2020), since it measures the thermal radiation emitted from the surface of the body (Roberto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [ 49 ], in Mato Grosso do Sul, Brazil, the presence of native trees reduced thermal load by 24.0% in July, 16.3% in August and 29.6% in September. In the same study, an integrated system with eucalyptus shade reduced thermal load by 17.0% in July, 4.6% in August and 7.5% in September.…”
Section: Discussionmentioning
confidence: 99%
“…The thermograms were then examined using Flir Tools software, version 6.3, with the Rainbow HC palette chosen. The operator used the camera at eye level, always maintaining consistency and without the aid of a tripod, focusing perpendicular to the target, following the methodological guidelines proposed by Barreto et al [ 49 ] and Silva et al [ 50 ].…”
Section: Methodsmentioning
confidence: 99%